2010
DOI: 10.1111/j.1746-1561.2009.00485.x
|View full text |Cite
|
Sign up to set email alerts
|

Body Dissatisfaction, Dietary Restraint, Depression, and Weight Status in Adolescents

Abstract: Psychopathology in obese youth is well known in clinical samples but this study suggests that obese youth in the community may be at increased risk of developing body dissatisfaction, dietary restraint, and depressive symptoms compared with overweight or normal weight youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
165
3
12

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(193 citation statements)
references
References 33 publications
13
165
3
12
Order By: Relevance
“…Regarding the feelings of dissatisfaction towards the weight perception, we found that the adolescents that describe themselves as about the right weight and slightly overweight are the ones referring to be trying to do something to lose weight more frequently, we could say, they might be the most unsatisfied with their bodies, result that agrees with the mentioned by other studies that point out that the adolescents with higher weight tend to be more unsatisfied and therefore to apply more dietary restrictions aiming to lose weight (Goldfield, Moore, Henderson, Buchholz, Obeid, & Flament, 2010). However, other research has also found that a high number of the adolescents that perceive themselves as normal weigh are also currently trying to lose weight, result probably explained for the existing preference for thinness as an indicator of beauty, more significantly present in the Western culture, expectation that could play an important role in the development of internalizing problems among the adolescents, when the ideal body does not match with the perceive one (Almeida, Severo, Araújo, Lopes, & Ramos, 2012).…”
Section: Discussionsupporting
confidence: 81%
“…Regarding the feelings of dissatisfaction towards the weight perception, we found that the adolescents that describe themselves as about the right weight and slightly overweight are the ones referring to be trying to do something to lose weight more frequently, we could say, they might be the most unsatisfied with their bodies, result that agrees with the mentioned by other studies that point out that the adolescents with higher weight tend to be more unsatisfied and therefore to apply more dietary restrictions aiming to lose weight (Goldfield, Moore, Henderson, Buchholz, Obeid, & Flament, 2010). However, other research has also found that a high number of the adolescents that perceive themselves as normal weigh are also currently trying to lose weight, result probably explained for the existing preference for thinness as an indicator of beauty, more significantly present in the Western culture, expectation that could play an important role in the development of internalizing problems among the adolescents, when the ideal body does not match with the perceive one (Almeida, Severo, Araújo, Lopes, & Ramos, 2012).…”
Section: Discussionsupporting
confidence: 81%
“…9 This association might be mediated by bullying or chronic stress; the underlying mechanism is still unclear. 34 Depressive symptoms were also associated with lifetime prevalence of smoking and alcohol intake in our sample. A study by Goodman found that smoking was strongly associated with a higher probability of developing depressive symptoms.…”
Section: Discussionmentioning
confidence: 85%
“…En la relación severidad de la obesidad y riesgo de un TCA, encontramos, a diferencia de lo publicado en la literatura [34][35][36][37][38][39] , sólo una tendencia a ser mayor en los pacientes más obesos. Pero, lo que si se observó fue que los adolescentes con mayor severidad de su obesidad presentan puntajes más altos del test EDI-2, lo que indica una mayor sintomatología de riesgo de trastornos alimentarios.…”
Section: Discussionunclassified
“…Consideramos, al igual que otros autores [39][40][41] , que es la suma de escalas alteradas lo que determina riesgo de un trastorno alimentario, y no la sola insatisfacción corporal que estaría más relacionada con la obesidad. Este estudio presenta limitaciones que deben ser consideradas.…”
Section: Discussionunclassified